Faktor-Faktor yang Berhubungan dengan Terjadinya Insiden Keselamatan Pasien di Ruang Kamar Bedah - Filda Mayang Sari; Dwi Retno Sulistyaningsih; Erna Melastuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The operating room is a hospital unit with a high risk to patient safety; therefore, the implementation of patient safety is a crucial indicator of healthcare quality. However, patient safety incidents continue to occur and are influenced by factors such as communication, leadership, knowledge, attitudes, motivation, and incident reporting practices. This study aimed to analyze the factors affecting patient safety incidents in the operating room of RS Sari Asih Ciputat. This research employed a quantitative correlational analytic design with a cross-sectional approach. The sample consisted of 35 nurses selected using total sampling. Research instruments included questionnaires on incident perception, reporting attitudes, work motivation, leadership based on the Leader–Member Exchange model, and incident reporting aligned with the International Patient Safety Goals. The results showed that most respondents were aged 17–25 years, female, held a diploma degree, had less than five years of work experience, and were permanent employees. Most respondents demonstrated poor perceptions and negative attitudes, while motivation and leadership were generally rated as good. Statistical analysis revealed a significant relationship between perception, attitude, motivation, and leadership and patient safety incidents in the operating room, with a p-value of 0.000.